Privilegi librari ed edizioni privilegiate nella Repubblica di Venezia (1527-1565) - Squassina, Erika (Milano University Press, 2022)
This work provides the legal framework in which the Venetian book trade operated in the years 1527-1565. The repertoire documents the systematic use that authors and printers made of the privileges system to ensure exclusivity in the economic exploitation of a work and thus protect their work and investments. The archival and bibliographic sources collected in this volume testify to the entrepreneurial strategies implemented by authors and printers to innovate and diversify publishing production in order to create products capable of competing on foreign markets. The repertoire also traces the role of the Venetian State in promoting and protecting the local book industry in a context characterized by constant historical and political changes.